Frequency of Diarrheagenic Virulence Genes and Characteristics in Escherichia coli Isolates from Pigs with Diarrhea in China - Yang, Gui-Yan (Microorganisms, 2019)
Intestinal pathogenic Escherichia coli (InPEC) is a leading cause of postweaning diarrhea (PWD) in pigs. Here, a total of 455 E. coli strains were isolated from small intestinal content or feces from pigs with PWD in 56 large-scale (>500 sows; 10,000 animals per year) swine farms between 2014 and 2016. The frequency of occurrence of selected virulence factors for InPEC pathotypes was detected in 455 isolates by real-time PCR. Sequence types (STs), pulsed-field gel electrophoresis (PFGE), and antimicrobial susceptibility profiles of 171 E. coli isolates from 56 swine farms were further determined. The heat-labile enterotoxin (LT) was the most common (61.76%), followed by heat-stable enterotoxin (STb) (33.19%), stx2e (21.54%), STa (15.00%), eae (8.98%), cnf2 (5.71%), stx2 (5.71%), F18 (3.25%), and F4 (2.25%) with rates varying by geographic area and year of isolation. Notably, hybrids of E. coli isolates were potentially more virulent, as some InPEC hybrids (virotype F18:LT:eae:stx2e) can rapidly cause cell death in vitro. Genotypic analysis revealed that the most prominent genotype was ST10 (12.87%). The PFGE patterns were heterogeneous but were not ST or virotype related. A total of 94.15% of isolates were multidrug-resistant, with average resistance rates ranging from 90.05% for nalidixic acid to 2.34% for meropenem. Our investigation contributes to establishing the etiology of diarrhea and developing intervention strategies against E. coli-associated diarrheal disease in the future.